KETERAMPILAN LEMPAR TANGKAP DALAM OLAHRAGA SOFTBALL BERBASIS AUDIO VISUAL - Juditya, Silvy; Agusni, Dhani (Jurnal Olahraga, 2018)
The purpose of this study was to determine the effect of audio visual on the results of throwing in softball games at Altras Baseball Softball Club. This study uses an experimental method, with a One Shot Case Study research design. The population in this study were adolescent athletes at the Altras Baseball Softball Club, the sample taken was 15 newbie athletes at the Altras Baseball Softball Club in South Tangerang. This study was conducted 12 meetings for 4 weeks with a number of exercises 3 times a week. The instrument used is the results of the top throw test in softball games. Based on the results of data processing and analysis of the results of the discussion of the study and analysis of data from the results of the research collected, it can be concluded as follows: Finding the average throwing test results are 32.2 with a maximum average of 2.6 and the minimum is 1.2 and the standard deviation: 6, 94 while the results of the catching throw test at the altras baseball softball club in south Tangerang are the most dominant category with the highest percentage of 40%. The results of the catching throw test at the Altras baseball softball club which are categorized as Excellent are 40%, Good category 20%, Sufficient by 26%, Less with a percentage of 7%, while Less Once is 7%.